Acute myocardial infarction-like event in a young patient with biventricular arrhythmogenic cardiomyopathy - Y. V. Stavtseva; E. A. Mershina; T. V. Lobzhanidze; E. I. Bazdireva; N. I. Khutsishvili; Zh. D. Kobalava (Столичная издательская компания, 2024)
The article describes a clinical case of biventricular arrhythmogenic cardiomyopathy (ACM) presented with myocardial infarction (MI) - like event in a young patient. The patient was hospitalized with suspected acute coronary syndrome and an episode of ventricular tachycardia (VT). Based on increased cardiac troponin, left ventricular systolic dysfunction with wall motion abnormalities, and nonobstructive coronary arteries the initial diagnosis of type 2 MI was made. To verify the etiology behind VT and ventricular structural abnormalities cardiac magnetic resonance imaging (MRI) was performed. Abnormalities of both right and left ventricles demonstrated by MRI and supported by the genetic testing established the diagnosis of biventricular ACM. Since the diagnosis was made, initially diagnosed MI was reassessed in favor of acute myocardial injury as a characteristic of ACM course. ACM should be included into differential diagnosis with MI and acute myocarditis in patients with elevated troponin and nonobstructive coronary arteries.